2018
DOI: 10.1016/j.jcf.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric assessment of pediatric patients with cystic fibrosis

Abstract: This is the largest comprehensive analysis of all types of hearing loss in pediatric patients with CF. Our data suggest that children with more severe sinus disease may be at lower risk for inflammatory middle ear disease and subsequent hearing loss. Patients who develop complications of CF such as diabetes should be monitored frequently, and the use of ototoxic drugs should be limited if possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…In contrast, all individuals in the control group had normal hearing from 0.25 to 8 kHz by the more conservative criterion. In a large retrospective study of hearing impairment, Kreicher et al (2018) reported 31.8% of individuals with CF (mean = 8.3 yr.) had hearing loss in at least one ear (>15 dB HL at any frequency from 0.25 to 8 kHz). Most ears with hearing loss showed a slight to mild loss (15%) with a smaller number of moderate to profound losses (3%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, all individuals in the control group had normal hearing from 0.25 to 8 kHz by the more conservative criterion. In a large retrospective study of hearing impairment, Kreicher et al (2018) reported 31.8% of individuals with CF (mean = 8.3 yr.) had hearing loss in at least one ear (>15 dB HL at any frequency from 0.25 to 8 kHz). Most ears with hearing loss showed a slight to mild loss (15%) with a smaller number of moderate to profound losses (3%).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted May 5, 2020. ; https://doi.org/10.1101/2020.04.29.20084848 doi: medRxiv preprint retrospective examination of the prevalence and type of hearing loss in the pediatric CF population, 31.8% had hearing loss in at least one ear in the SF region (Kreicher et al, 2018). Further analysis of the type of hearing loss (considering each ear separately) showed that 74.1% had normal hearing, 5.3% had conductive loss, 2.3% sensorineural loss, 5.1% mixed hearing loss, and 13.2%…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Audiological data analyses were adapted from previous AudGenDB studies . Pure‐tone air‐ and bone‐conduction audiometry and sound‐field testing were used to evaluate hearing outcomes.…”
Section: Methodsmentioning
confidence: 99%